MAKNA DAN PENGHAYATAN SAKRAMEN EKARISTI BAGI CALON KATEKIS - Marsia Juna; Agustinus Wisnu Dewantara (Lembaga Penelitian STKIP Widya Yuwana, 2019)
The Eucharist is the source and summit of the entire Christian life (LG 11). The Eucharist is said to be a source of life because in that celebration people gain the powerof life from the proclaimed word. The Eucharist is said to be the summit because the whole life of the Christian community is fixed and leads to the Eucharist as the apex.STKIP Student Widya Yuwana Madiun is formed as a catechist who will proclaim Christ, so it is important to always follow the Eucharist. Many students celebrate theEucharist with the wrong motives that they consider the Eucharistic celebration to be the obligation of the campus, even tends to choose not to attend. Based on thatbackground, the researcher wants to see how the students understand about the Eucharistic sacrament, what is the student's motivation to engage in the Eucharisticcelebration held by the campus, and what is the sacrament of the Eucharist for the students. This research uses qualitative method. Data collection techniques usedin this study is structured interviews. Based on the data analysis, the result of the research and conclusion are as follows: theoretically the students have understood andknow about Eucharistic sacrament, the motivation in following the Eucharistic celebration, and the meaning of the Eucharistic sacrament. But most students have notloved the Eucharist in their lives. Researchers have proposals and suggestions based on the following conclusions: For the development of theological knowledge, this research is expected to be followed up with various coaching and new methods more deeply so that the compulsion is not attached to the students and students also love the Eucharist in daily life. Subsequent research is also expected to follow up on the results of this study to find the reasons why most students still feel lazy and forced to follow the Eucharistic celebration held by the campus and the solution of the problem of laziness and compulsion.